ANALISIS TATA KELOLA RESTRIBUSI PARKIR SEBAGAI UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH KOTA BANDA ACEH - Muazzinah, Muazzinah; Ade, Amuji (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2020)
This study aims to learn how to manage public roadside parking in an effort to increase Local Revenue from parking fees in Banda Aceh City and obstacles to managing public roadside parking in Banda Aceh City. This research method uses qualitative research methods with the type of descriptive research. The informants of this study consisted of the Banda Aceh City Transportation Agency, parking attendants, and the community. Data collection techniques are done by interview, observation, and documentation. The results of research that can be published on roadside parking by the Banda Aceh City Transportation Office have been classified as transparent because any information about roadside parking can be accessed directly by the public through the Banda Aceh City Transportation Department website but it is still lacking in transparency. Accountability Management of roadside parking is also full of responsibility because every service officer and parking attendant is given training and guidance and even supervision. The responsibility for parking management also exists because of the existence of faith in the form of reports with the help of community members who issue them. Parking management independence is seen as a compilation of decisions without personal interests so that one party is not interrelated if there is a parking attendant who has a problem. Monitoring activities of parking attendants and cracking down on parking attendants who have problems without any maintenance difference. The obligation to manage parking always takes into account the interests of the field and the community based on the principle of equality and fairness.